La grabación de las actuaciones en fase de instrucción. La decisión sobre su forma y modo de documentación. La transcripción de lo grabado (Acta Judicial Journal, 2018)
This study tries to examine the implementation of new technologies on the field of criminal justice. The current legislation based on the Organic Law of the Judiciary and later, is analyzed. The Article 9 of the Spanish Constitution establishes the legal certainty as a basic principle. The article 24 sets the right to a public trial without any undue delay and all legal guarantees.The criminal proceedings recorded under this legal frame, guarantees the orality and attributes to those proceedings the character of trustworthy, reliable, and irrefutable, since they are substantiated on an unchangeable and unalterable recording system, attested by the Judicial Administration Counselor.
Keywords: Recording, Transcription, Documentation, Orality, Legal security